PSEUDOESCORPIONES FORÉTICOS DE ROEDORES EN MÉXICO - Villegas-Guzman, Gabriel A.; Hernández-Betancourt, Silvia (Instituto de Ecología, A.C., 2006)
We report on new hosts and new localities of pseudoscorpions of the genus Epichernes Muchmore, 1982. The three known species of this genus have been found on rodents of the family Heteromyidae. This is the first time that E. aztecus Hentschel, 1982, has been collected on Liomys irroratus Gary, 1868, and L. pictus Thomas, 1893, from the states of Nuevo Leon and Durango, respectively. We found E. navarroi Muchmore, 1990, on Heteromys gaumeri Allen, 1897, in Yucatan; this is a new locality for this pseudoscorpion previously known only from Quintana Roo on the same rodent species.